Naturalism and democracy: a commentary on Spinoza's political treatise in the context of his system - Bartuschat, Wolfgang; Kirste, Stephan; Walther, Manfred; Fontini, James (Brill, 2019)
Spinoza's ontology and epistemology as background to his political theory / Wolfgang Bartuschat -- Political philosophy as theory of praxis / Stephan Kirste and Manfred Walther -- Natural and state right, or, Spinoza's foundation of practical reason / Gunnar Hindrichs -- Spinoza's theory of sovereignty / Oliver W. Lembcke -- Spinoza's theory of international relations / Tilmann Altwicker -- Right and reason in Spinoza's political philosophy on the tasks and limits of state authority / Tobias Herbst -- Theory of the best state / Martin Leiner -- Institutional design to stabilize the state : theory of the (constitutional) monarchy / Manfred Walther -- Theory of the aristocracy / Wolfgang Bartuschat -- Spinoza's theory of absolute democracy / Rainer Keil -- The political treatise in present discussion / Tilman Reitz
Includes bibliographical references and index
Keywords: Spinoza, Benedictus de -- 1632-1677 -- Tractatus politicus -- Congresses; Kommentar; Spinoza, Benedictus de / Tractatus politicus